Are the Ingredients of a Developmental State Applicable to South Africa? (The Strategic Review for Southern Africa, 2020)
The effective functioning of institutions is the hallmark of a developmental state globally. This is because institutions have a key role to play in the implementation of policies and the delivery of public goods. One of the fundamental roles played by institutions is the coordination of government interventions. In the absence of such, policy implementation and service delivery will not be rational. For coordination to take place, governments all over the world need to enter into partnership with other societal players such as business, labour and civil society. In essence, the idea developmental states requires that states enter into social contracts on the basis of long-term national developmental goals in partnership with other developmental partners. However, the state should be able to play a guiding role in pursuit of national developmental goals. In order for the state to effectively play this role, it needs to insulate itself from external influence and pressure. It should also be able to appoint its personnel based on merit, so as to enable its bureaucracy to interpret and implement policy accordingly. The government should also establish powerful oversight structures capable of conducting checks and balances on the affairs of the state and its partners.
Keywords: Developmental State; Meritocratic Bureaucracy; National Development Plan; Social Contract; National Interest